Factors that Influence Mother's Motivation for Complete Basic Immunization for Infants - Rakhman, Nurhasanah Putri; Indriati, Ganis; Fitri, Aminatul (CV. Rayyan Dwi Bharata, 2024)
Introduction: Immunization is a program carried out by the government to actively increase the body's immunity in babies against certain diseases. Completeness of basic immunization for babies can be influenced by maternal motivation factors. Objective: This study aims to determine the factors that influence the complete status of basic immunization in infants. Method: Researchers used a correlation analytical research design with a cross-sectional approach. The population in this study were mothers who had babies aged 0-11 months in the working area of the RI Sidomulyo Community Health Center, Tampan District, Pekanbaru City. Sampling used accidental sampling technique with a total of 93 respondents. The analysis used is chi-square analysis. Results: Researchers found that the majority of mothers aged 26-35 years were 79 respondents (84.9%), had secondary education (SMA) as many as 54 respondents (58.1%), the majority of employment status was not working as many as 76 respondents (81.7%). %), had more than one child as many as 68 respondents (73.1%), had good knowledge as many as 72 respondents (77.4%), felt confident about immunization as many as 64 respondents (68.8%), had good family support as many as 68 respondents (73.1%), it was easy to reach health services for 86 respondents (92.5%), and 71 respondents (76.3%) had complete immunization status. Factors that influence maternal motivation, level of knowledge (p-value=0.0380.05), confidence (p-value=0.0000.05), and family support (p-value=0.0000.05), is a factor related to the completeness of basic immunization in infants. Conclusion: There are three factors related to the completeness of basic immunization in infants, namely the mother's level of knowledge, confidence, and family support. Suggestion: This research is expected to be a source of information and knowledge for the community, especially parents of infant children.